Graphium septentrionicolus Page & Treadaway, 2013 (Lepidoptera: Papilionidae) is a distinct species - Cotton, Adam M.; Doleck, Tenzing; Zhang, Xin; Inayoshi, Yutaka; Lohman, David J.; Hu, Shao-Ji (Zootaxa, 2022)
After molecular and morphological analyses, the taxon septentrionicolus Page & Treadaway, 2013 is shown to be a distinct species, and Graphium adonarensis (Rothschild, 1896) is placed as conspecific with Graphium sarpedon (Linnaeus, 1758). Graphium huangshanensis Wu & Ma, 2016 syn. nov. is synonymised with G. septentrionicolus.